We knew it all along! Using cognitive science to explain how andragogy works. Issue 3 (4th April 2016) - Hagen, Marcia; Park, Sunyoung
Abstract : Purpose: – This paper aims to link recent findings in cognitive neuroscience to better understand how andragogically informed instructional practices impact cognition and learning. Design/methodology/approach: – The research questions guiding the study is in what ways can the recent findings in cognitive neuroscience help to inform adult education theory, including andragogy in particular, to deepen our understanding of how andragogical instructional principles and practices can improve learning? We adopted Torraco's (2005) integrative literature review approach of providing enough details regarding the selection of the literature and the identification and verification of emerged themes of main ideas. Findings: – The core assumptions of andragogy (self-direction, prior experience, readiness to learn and immediacy of application) have a connection to the neural networks related to memory and cognition. Research limitations/implications: – First, this study provides fundamental foundations for combining cognitive neuroscience and adult learning to illuminate how cognitive neuroscience contributes physiologically to adult learning. Second, the findings in cognitive neuroscience related to the four assumptions for andragogy help to provide scientific explanations and interpretations for adult learning theories influencing human resource development (HRD), such as self-directed learning, experiential learning and role theory. Practical implications: – First, HRD practitioners could use the integrative approach between andragogy and the cognitive neuroscience to reduce the issues of learning activities in generation differences. In addition, cognitive neuroscience research may contribute to improving teaching and instructional techniques. Originality/value: – The contributions of this study is that it provides an integrative review about why and how anagogical principles work through the lens of cognitive neuroscience. Based on the findings, we suggested a model of adaptive cognitive neuroscience-adult learning structures.